Distance learning for training business game tutors - Marinho, Mariana De Toledo [UNESP]; Rodrigues, José De Souza [UNESP]; Zambon, Katia Livia [UNESP]; Crepaldi, Antonio Fernando [UNESP] (Associação Brasileira de Engenharia de Produção, 2017)
This work is the result of research that proposes the incorporation of Distance Learning into a Business Game as a strategy to enhance tutor training, considering entrepreneurship difficulties faced by public school teachers. Part of the problem could be attributed to subject type, because, in general, it is not common to find entrepreneurship on school curricula. The Distance Learning (DL) activities were developed using the Moodle platform and structured by topic to increase educational flexibility and achieve a better balance between individual reflection and online discussion. It was developed in four steps: course content development; course evaluation by computer technicians; restructuring the course based on course evaluation done by computer technicians and course evaluation by teachers from the public school system. A preliminary test was performed with informatics technicians to technically evaluate the learning environment. Based on this, the course was restructured, applying corrections and adjustments to improve environment usability. After corrections, a final test was conducted with public school system teachers to analyze user perception, which gave a positive result. Virtual learning environment evaluation is complex and multidisciplinary, requiring the technical knowledge of internet programming and a conceptual knowledge of education, especially in the field of learning. When the evaluation done by teachers was examined, it was found that deficiencies pointed out by computer technicians had been resolved, giving a positive rating. This current research concludes that DL can improve the use of games, because it is possible to structure the content related to the learning gaps of specific groups of students. In this respect the use of games results can guide the development of content.
Keywords: Entrepreneurship; Business game; Distance learning course